Intercultural Education as a factor and a result of social change in Croatia - Bartulović, Marija pedagoginja (2008)
This paper provides a synthetic overview of the complex factors that shape the process of building an intercultural dialog in Croatia as a multicultural society, taking into account the specific socio-cultural context, war experience and political changes that took place in our recent history, as well as the global changes and developments in education worldwide, related to the process of globalization, internationalization, informational communication and expansion of liberal capitalism. In order to provide a theoretical background for the construction of intercultural curriculum, this paper analyses the scientific theories and conceptual models of interculturalism, in relation to the results of scientific research of Croatian educational practice in the area of intercultural education during last two decades, with special accent on the ongoing national project “ Intercultural Curriculum and/or Education in Languages of National Minorities” in organization of Institute of Pedagogy at Department of Pedagogy ( University of humanities and social sciences), directed towards implementation of democratic principles and intercultural sensitivity in our educational system. Important attention is also given to the problem of key-competence based teacher education, as a modern trend being built up on a paradigm of knowledge society and life-long learning, which can not be understood correctly without awareness of the importance that intercultural values have, as a basis of democratic oriented educational policies in modern society.
Projekt MZOS
ENG